Citrus reticulatae pericarpium Extract Decreases the Susceptibility to HFD-Induced Glycolipid Metabolism Disorder in Mice Exposed to Azithromycin in Early Life - Lu, Hanqi; You, Yanting; Zhou, Xinghong; He, Qiuxing; Wang, Ming; Chen, Liqian; Zhou, Lin; Sun, Xiaomin; Liu, Yanyan; Jiang, Pingping; Dai, Jiaojiao; Fu, Xiuqiong; et al. (Frontiers in Immunology, 2021)
BACKGROUND: Studies have showed that gut microbes' disorder in mice caused by early life antibiotic exposure promotes glycolipid metabolism disorder in the adulthood. However, its mechanism remains unclarified, and there is a lack of effective intervention. PURPOSE: The study was to investigate whether early life azithromycin (AZT) exposure in mice could promote high-fat diet (HFD)-induced glycolipid metabolism disorder in the adulthood, and Citrus reticulata pericarpium (CRP) extract could improve this glycolipid metabolism disorder by regulating the gut microbes in mice with early exposure to antibodies. METHODES and RESULTS: Mice of 3-week-old were treated with AZT (50 mg/kg/day) in drinking water for 2 weeks and subsequently fed with CRP diet (1% CRP extract) for 4 weeks and HFD for 5 weeks. The results showed that early life AZT exposure promotes HFD-induced glycolipid metabolism disorder, increases the levels of inflammatory, flora metabolism product trimethylamine N-oxide (TMAO), and microbes' disorder in adult mice, and CRP extract improves this process. CONCLUSION: Taken together, this study suggests that early life AZT exposure increases the susceptibility to HFD-induced glycolipid metabolism disorder in adult mice, and CRP extract could decrease the susceptibility to this mice by regulating the gut microbes.